Analysis of Magnetohydrodynamic Micropolar Nanofluid Flow due to Radially Stretchable Rotating Disk Employing Spectral Method. (24th February 2023) - Tulu, Ayele
Abstract : The present analysis is aimed at examining MHD micropolar nanofluid flow past a radially stretchable rotating disk with the Cattaneo-Christov non-Fourier heat and non-Fick mass flux model. To begin with, the model is developed in the form of nonlinear partial differential equations (PDEs) for momentum, microrotation, thermal, and concentration with their boundary conditions. Employing suitable similarity transformation, the boundary layer micropolar nanofluid flows governing these PDEs are transformed into large systems of dimensionless coupled nonlinear ordinary differential equations (ODEs). These dimensionless ODEs are solved numerically by means of the spectral local linearization method (SLLM). The consequences of more noticeable involved parameters on different flow fields and engineering quantities of interest are thoroughly inspected, and the results are presented via graph plots and tables. The obtained results confirm that SLLM is a stable, accurate, convergent, and computationally very efficient method to solve a large coupled system of equations. The radial velocity grows while the tangential velocity, temperature, and concentration distributions turn down as the value of the radial stretching parameter improves, and hence, in practical applications, radial stretching of the disk is helpful to advance the cooling process of the rotating disk. The occurrence of microrotation viscosity in microrotation parameters (A 1 − A 6 ) declines the radial velocity profile, and the kinetic energy of the fluid is reduced to some extent far away from the surface of the disk. The novelty of the study is the consideration of microscopic effects occurring from the micropolar fluid elements such as micromotion and couple stress, the effects of non-Fourier's heat and non-Fick's mass flux, and the effect of radial stretching disk on micropolar nanofluid flow, heat, and mass transfer.